El apalancamiento financiero y su relación con la rentabilidad en la Caja Municipal de Ahorro y Credito Maynas S.A. 2017-2023 - Ruiz Rivera, Cesia Keren-Hapuc (2025)
This research aimed to analyze the relationship between financial leverage and profitability in the Caja Municipal de Ahorro y Crédito Maynas S.A. during the period 2017–2023. Using a quantitative approach with a non-experimental, correlational, and longitudinal design, the study was based on quarterly financial data obtained from official sources such as the Superintendency of Banking, Insurance and AFPs (SBS) and the Central Reserve Bank of Peru (BCRP). Spearman’s rank correlation coefficient was applied to determine statistical associations between different measures of leverage (debt/assets, debt/equity, interest coverage) and profitability indicators (ROA, ROE, net margin). The findings revealed positive and statistically significant correlations, validating the general hypothesis: financial leverage has a direct relationship with profitability. These results differ from previous studies conducted in other business sectors, where the relationship was found to be weak or even negative. In the specific case of Caja Maynas, the strategic use of leverage contributed positively to profitability, indicating a favorable financial management approach. The study concludes with practical recommendations and proposals aimed at optimizing this relationship, offering valuable insight for improving decision-making processes regarding financing and capital structure within microfinance institutions.